Surgery for colloid carcinoma of the pancreas with portal vein tumor thrombus: a case report - Daisuke Udagawa; Motohide Shimazu; Tadayuki Sakuragawa; Shotaro Maruyama; Yusuke Uchi; Eisuke Miura; Yohei Masugi; Michiie Sakamoto (Surgical Case Reports, 2020)
Abstract Background The portal vein is occasionally invaded by advanced malignant tumors in the pancreatic head region. However, pancreatic cancer rarely has portal vein tumor thrombi. We report a case of pancreatic cancer with a massive portal vein tumor thrombus undergoing pancreatoduodenectomy with combined resection of the portal vein. Case presentation A 71-year-old man visited a clinic with complaints of abdominal discomfort and vomiting. Gastroscopy showed a massive tumor in the duodenum. He was referred to our hospital for further examinations and treatment. The CT showed a low-density tumor with a maximum diameter of 10 cm located on the pancreas head. A tumor widely invaded the duodenum and had a 6-cm portal vein tumor thrombus. MRCP did not show obvious stenosis of the pancreatic duct due to tumor invasion. There were no findings suggesting distant metastases. Biopsy of the duodenum revealed adenocarcinoma. He was diagnosed with primary pancreatic cancer or duodenal cancer with portal vein tumor thrombus and underwent pancreatoduodectomy with resection and reconstruction of the portal vein. He suffered no postoperative complications and was discharged 2 months after surgery. The final histopathological diagnosis was pancreatic colloid carcinoma. He received adjuvant chemotherapy, but died 16 months after surgery. Conclusions Colloid carcinoma of the pancreas is rare, and pancreatic carcinoma seldom forms a portal vein tumor thrombus. We experienced a very rare case of pancreatic colloid carcinoma with portal vein tumor thrombus and performed radical resection of the pancreas and portal vein.